Structure preserving Multi-Contact Balance Control for Series-Elastic and Visco-Elastic Humanoid Robots - Werner, Alexander; Henze, Bernd; Keppler, Manuel; Loeffl, Florian; Leyendecker, Sigrid; Ott, Christian (2018 IEEE/RSJ INTERNATIONAL CONFERENCE ON INTELLIGENT ROBOTS AND SYSTEMS (IROS), 2018)
This paper proposes an integration of multi-body and actuator control for multi-contact balancing for robots with highly elastic joints. Inspired by the structure preserving control concept for series-elastic fixed-base robots, the presented approach aims to minimize the control effort by keeping the system structure intact. Balancing on multiple contacts requires to solve the force distribution problem. In locomotion, contacts change quickly, requiring a swift redistribution of contact forces. This is a challenge for elastic robots as the actuator dynamics and limits prevent instantaneous changes of contact forces. The proposed dynamically consistent force distribution is implemented as a model predictive controller which resolves redundancy while complying with contact force and actuator constraints.<br
CRIS-Team WoS Importer:2019-03-08
Keywords: Force; Actuators; Robot kinematics; Dynamics; Task analysis; Humanoid robots